One shot at forever [compact disc, unabridged] : a small town, an unlikely coach, and a magical baseball season - Ballard, Chris (Tantor Media, 2012)
In 1971, a small-town high school baseball team from rural Illinois playing with hand-me-down uniforms and peace signs on their hats defied convention and the odds. Led by an English teacher with no coaching experience, the Macon Ironmen emerged from a field of 370 teams to become the smallest school in Illinois history to make the state final-- a distinction that still stands. Chris Ballard tells the story of the team and its unlikely coach-- a hippie, dreamer, and intellectual.